Criminal Behavior as a Basis for Criminal Responsibility for the Crime of Introducing Substances Hazardous to the Environment in Jordanian Legislation - ALKHSEILAT, Abdullah; AL-BILLEH, Tareq; ALMANASRA, Majd; ALWERIKAT, Naji (Journal of Environmental Management and Tourism, 2022)
The aim of the research is to clarify the conditions of criminal behaviour appropriate to determine the criminal liability for the crime of introducing waste and hazardous substances to the environment, the research problem lies in the fact that most penal legislation still assesses criminal liability for the introduction of waste, and hazardous substances to the environment on the basis that these harmful substances and wastes were introduced in a direct, and certain manner, whereas the methods of the indirect introduction of these harmful substances and wastes were not taken into account, which found a legislative loophole in which the offender avoids criminal liability for his criminal behaviour by introducing substances that are hazardous to the environment, in addition to highlighting the impact of written or oral approval or licenses on the introduction of hazardous substances and waste on criminal behaviour and identifying those criminally responsible for polluting the environment. The research followed the analytical approach, by analysing the provisions regulating the subject of this research, and the research came out with several results and recommendations, the most important of which is that criminal liability for the introduction of waste and hazardous substances does not require direct harm, and the mere introduction of hazardous substances and waste to the environment is a serious crime.